Associations of health literacy with metabolic status and quality of life among comunity patients with type 2 diabetes in Shanghai - YANG Liping; SONG Haihong; SHEN Jue; GAO Jinli; ZHANG Zhiping; QIAN Liuyu; GONG Huan (Shanghai yufang yixue)
ObjectiveTo investigate the current status of health literacy among type 2 diabetes mellitus patients in Shanghai communities, to analyze its correlation with glycemic and lipid metabolic indicators and quality of life (QoL), and to provide an evidence for the development of effective intervention measures.MethodsA follow⁃up survey was conducted among diabetic patients diagnosed at hospitals above the secondary level from March to June, 2023, who were part of a diabetes cohort study jointly established by Songnan Community in Baoshan District and the Shanghai Institute of Endocrinology. Patients were assessed using a simplified evaluation form for diabetes-related health literacy and a QoL scale, and metabolic indicators such as blood glucose and blood lipids were measured. Pearson correlation coefficients were employed to assess the relationship between health literacy levels and metabolic indicators as well as QoL. Logistic regression models were used to estimate the odds ratios (OR) and 95% confidence intervals (CI) for the associations between patients’ health literacy levels, metabolic status, and QoL.ResultsAmong the 932 diabetic patients surveyed, the health literacy level was low, with an average score of (65.2±13.4) points of which (62.6±13.8) points for males and (67.9±12.5) points for females. The average QoL score was (44.1±9.2) points of which (44.0±9.5) points for males and (44.2±8.9) points for females. The achievement rates of HbA1c, total cholesterol (TC), and triglycerides (TG) were 51.6%, 30.3%, and 64.8%, respectively. The TC achievement rate among male patients (37.6%) was significantly higher than that among females (22.8%). Significant differences in HbA1c achievement rates were observed across age groups, education levels, disease durations, and BMI levels (P<0.05). Similarly, significant differences were found in FPG achievement rates across different age groups, annual household incomes, disease durations, and family histories (P<0.05). No statistically significant differences were noted in TG and HDL-C achievement rates across all variables (P>0.05). However, LDL-C achievement rates were significantly higher in patients without complications compared to those with complications (P<0.05). Health literacy showed a significant negative correlation with psychological dimension, treatment dimension, and QoL scores (r=-0.14, P<0.05). After adjusting for potential confounding factors, a significant association was found between patients’ health literacy levels and QoL, but not with metabolic indicators.ConclusionThere is a significant correlation between health literacy levels and QoL among diabetic patients in community settings. Further exploration is needed to identify factors influencing patients’ QoL and glycemic and lipid metabolic indicators.